THE EFFECT OF ENTREPRENEURIAL COMPETENCE ON THE GROWTH OF SME: THE MEDIATING ROLE OF NETWORK COMPETENCE - Cuaca, Jeffrey Prasetya; Wijaya, Andi (International Journal of Application on Economics and Business, 2024)
This study aims to investigate the influence of entrepreneurial competencies, with a focus on strategic and ethical competencies, on business growth. It also explores the mediating role of network competencies in this context. The sample consisted of 134 respondents from Tanjung Duren, West Jakarta, selected through purposive sampling. The findings indicate a positive and significant relationship between strategic competencies and business growth, while ethical competencies had no significant impact on business growth. Additionally, both strategic and ethical competencies were found to positively and significantly influence network competencies, which, in turn, had a positive and significant effect on business growth.